Selective memory and behavioral alterations after ambient ultrafine particulate matter exposure in aged 3xTgAD Alzheimer’s disease mice - Katrina Jew; Denise Herr; Candace Wong; Andrea Kennell; Keith Morris-Schaffer; Günter Oberdörster; M. Kerry O’Banion; Deborah A. Cory-Slechta; Alison Elder (Particle and Fibre Toxicology, 2019)
Abstract Background A growing body of epidemiological literature indicates that particulate matter (PM) air pollution exposure is associated with elevated Alzheimer’s disease (AD) risk and may exacerbate AD-related cognitive decline. Of concern is exposure to the ultrafine PM (UFP) fraction (≤100 nm), which deposits efficiently throughout the respiratory tract, has higher rates of translocation to secondary organs, like brain, and may induce inflammatory changes. We, therefore, hypothesize that exposure to UFPs will exacerbate cognitive deficits in a mouse model of AD. The present study assessed alterations in learning and memory behaviors in aged (12.5 months) male 3xTgAD and non-transgenic mice following a 2-week exposure (4-h/day, 4 days/week) to concentrated ambient UFPs using the Harvard ultrafine concentrated ambient particle system (HUCAPS) or filtered air. Beginning one month following exposure, locomotor activity, spatial learning and memory, short-term recognition memory, appetitive motivation, and olfactory discrimination were assessed. Results No effects on locomotor activity were found following HUCAPS exposure (number concentration, 1 × 104–4.7 × 105 particles/cm3; mass concentration, 29–132 μg/m3). HUCAPS-exposed mice, independent of AD background, showed a significantly decreased spatial learning, mediated through reference memory deficits, as well as short-term memory deficits in novel object recognition testing. AD mice displayed diminished spatial working memory, potentially a result of olfactory deficits, and short-term memory. AD background modulated HUCAPS-induced changes on appetitive motivation and olfactory discrimination, specifically enhancing olfactory discrimination in NTg mice. Modeling variation in appetitive motivation as a covariate in spatial learning and memory, however, did not support the conclusion that differences in motivation significantly underlie changes in spatial learning and memory. Conclusions A short-term inhalation exposure of aged mice to ambient UFPs at human-relevant concentrations resulted in protracted (testing spanning 1–6.5 months post-exposure) adverse effects on multiple memory domains (reference and short-term memory) independent of AD background. Impairments in learning and memory were present when accounting for potential covariates like motivational changes and locomotor activity. These results highlight the need for further research into the potential mechanisms underlying the cognitive effects of UFP exposure in adulthood.